Memory for orientation in the natural environment - Martin, M; Jones, G (1997)
Previous work has demonstrated that memory for information to which people have been exposed for a prolonged period in everyday life may be very poor. One interpretation of such findings is that we tend to remember only information that is likely to be of future functional relevance. However, it is also noticeable that previous investigations have in general studied memory concerning artefacts of arbitrary design rather than the natural environment. As the product of an evolutionary process, it is possible that memory is in general adapted towards dealing with the natural rather than the artificial. For example, in the case of one frequently encountered artefact it has been shown that people retain little information as to whether the head on a coin faces to left or right. The present study probed a naturally occurring counterpart to this, by examining recall of the orientation of the crescent moon. For a new moon it is the right-hand side of the moon that is illuminated whereas for an old moon it is the left-hand side, in the northern hemisphere. The results of Experiment 1 indicated no retention of this information by participants (though, as the results of Experiment 4 confirmed, participants did remember that the new and old moons have opposite orientations). The results of Experiments 2 and 3 confirmed the absence of retention when recall was cued by reference to the solar cycle rather than the lunar cycle, either singly or in combination. It is concluded that, contrary to expectation, memory for the natural environment is in this case no better than memory for the artificial environment, consistent with the primary role in determining the content of everyday memory being taken by functional relevance. © 1997 by John Wiley and Sons, Ltd.